Ocena razvoja Zgornje Gorenjske z vidika okoljske, socialne in ekonomske trajnosti - Ferreira, Andreja (Geografski vestnik, 2006)
The sustainability of the development of the Upper Gorenjska region and its landscape-ecological units was assessed with the aid of the model prepared specially for these needs and equipped with the relevant indicators from the environmental, social and economic spheres. The development of the Upper Gorenjska region as a whole was assessed as favourable, less favourable are inadequacies on all spheres of development and obvious differences between its central and remote areas.
Keywords: Slovenia; Slovenija; Gorenjska; Upper Carniola; kulturna pokrajina; pokrajinska ekologija; sonaravni razvoj; sustainable development; trajnostni razvoj; regionalni razvoj; ekonomski razvoj